Utilization of Tourism Potential in Improving the Economy in The City of Bontang Region to Support Economic Stability - Asiah, Afifah Nur; Amalina, Endah Nur (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This study aims to determine the management and utilization of Bontang Kuala tourism and its economic impact. This study uses a qualitative approach. The informants for this study were the Head of the Bontang City Tourism and Sports Youth Service, the Head of the Tourism Sector, the Head of the Development Section, Tourism Object Development & Creative Economy, Bontang Kuala Village Head, Culinary Business Owners, the community around the tourist attraction, and tourists were determined using purposive sampling. Data collection techniques used are observation, interviews, and documentation. Data analysis was carried out through five stages of activity, including preparing and organizing data, exploring and coding data, building descriptions, representing and reporting findings, interpreting findings, and validating the accuracy of conclusions. Well, they start from the provision of facilities and infrastructure, promotion and marketing strategies, as well as cooperation with various parties. In addition, Bontang Kuala tourism is also utilized in cultural heritage, nature, and cultural tourism, which has a good impact on the community's economy. Finally, this also affects regional economic stability